Sport-selfies: Characteristics and differences in gender, ethnic and national origin, type, form, and milieu of sports. Issue 2 (4th May 2019) - Szabo, Attila; Buta, Levente
Abstract : Selfie posting on social media is a modern-day phenomenon. There are over a thousand academic articles on selfies, but sport-selfies have not been examined to date, even though they might have a 'positive message' in popularizing sports and exercise. This exploratory work assessed the nature and origin of sport-selfies. After a content analysis of 930 random sport-selfies, it emerged that while sports are dominated by men, women post more sport-selfies than men. Over 90% of the posts portray adults who present themselves in individual and recreational sports. Outdoor and land-based sport activities are the most frequent. In contrast to research on selfies in general, sport-selfies are primarily posted by White individuals. Most sport-selfies originate from three nations: Germany, Brazil, and Russia. Images linked to body conditioning are the most popular. It appears that sport-selfies are culture, gender, and sport specific. The present results may stimulate interest in determining the reasons behind them.